2022
DOI: 10.1016/j.ehb.2021.101104
|View full text |Cite
|
Sign up to set email alerts
|

School starting age and nutritional outcomes: Evidence from Brazil

Abstract: Recent studies reported that the age of primary school enrolment is a major driver of educational achievement and adult income, but its impacts on childhood health and nutrition remain largely unknown, particularly in developing countries where childhood stunting and overweight coexist. In Brazil, children are supposed to enrol in primary school the year they turn 6. Using a database of middle school students in Brazil based on a 2015 survey, I implemented an instrumental variables strategy using quasi-exogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 40 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…The three of the four articles from Türkiye were published between 2017 and 2019, when the country implemented legislative changes to school-entry age ( Gökçe et al, 2017 ; Öner et al, 2018 , 2019 ). The remaining studies used data from Brazil, Mexico, and Vietnam ( Caudillo, 2019 ; Caye et al, 2020 ; Levasseur, 2022 ; Nguyen & Lewis, 2019 ). All the LMIC studies included therefore were from upper-middle-income economy countries, except Vietnam which is lower-middle-income economy country ( Nguyen & Lewis, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The three of the four articles from Türkiye were published between 2017 and 2019, when the country implemented legislative changes to school-entry age ( Gökçe et al, 2017 ; Öner et al, 2018 , 2019 ). The remaining studies used data from Brazil, Mexico, and Vietnam ( Caudillo, 2019 ; Caye et al, 2020 ; Levasseur, 2022 ; Nguyen & Lewis, 2019 ). All the LMIC studies included therefore were from upper-middle-income economy countries, except Vietnam which is lower-middle-income economy country ( Nguyen & Lewis, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…There were no low-income economy country studies, and no published studies identified from the African continent. The exposure was generally defined as being young-for-grade ( Caudillo, 2019 ; Caye et al, 2020 ; Gökçe et al, 2017 ; Gümüş & Yürümez, 2021 ; Nguyen & Lewis, 2019 ; Öner et al, 2018 , 2019 ), with the exception of one quasi-experimental study from Brazil ( Levasseur, 2022 ), which defined the exposure as late enrollment compared to peers in the same grade (as opposed to early enrolment). In terms of outcomes, all 8 studies assessed health outcomes among children and youth aged between 0 and 22 years ( Caye et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations